When graffiti is not art: the damage of alkyd sprays on calcareous stones employed in cultural heritage - Dionísio, Amélia (2022)
In order to evaluate the damage of alkyd sprays on calcareous monument stones, limestone and marble samples of renowned building materials and ornamental stones in the Portuguese architecture, Lioz and Branco, were submitted to artificial graffiti. The harmfulness was assessed in relation to the variation of water vapour permeability, static contact angle, water microdrop absorption, chromatic changes and surface contact roughness. For evaluation of the degree of the aerosol’s penetration into the stone and the morphological surface changes, Scanning Electron Microscopy was used. Apart from the aesthetics aspects, which threaten the historical significance of the monument, the current research has shown that alkyd sprays used in graffiti interact with the stone substrate by reducing the water vapour permeability of the studied stones and thus leading to water condensation just underneath the paint. Moreover a significant reduction of the roughness of the stone surfaces is generated by the application of these paintings, creating a smooth and uniform overcoat that modifies surface texture and the details intentionally left in the original work of art. The water repellency of the stone surfaces is also significant incremented. An increase knowledge of the interaction of alkyd sprays with stone materials provides valuable insight and greater understanding of the vulnerability of stone to graffiti vandalism, namely to some Portuguese monument stones.